2022
DOI: 10.3389/fpsyg.2022.866103
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Causality and Pronoun Resolution in Intersubjective Discourse Relations

Abstract: Interpersonal verbs like disappoint and praise in Lucy disappointed/praised Mary because she… bias the potential cause of the event to one of the antecedent noun phrases (henceforth NPs) (e.g., Lucy for disappoint whereas Mary for praise). Using Chinese as its materials, this study investigated how verb-based implicit causality affects online pronoun resolution in backward concession (e.g., Lucy disappointed/praised Mary although she…), an intersubjective discourse relation where the subordinate although-claus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Studies on implicit causality have demonstrated that the information encoded in the semantics of the verbs imposes constraints on causal attributions ( Crinean and Garnham, 2006 ; Bott and Solstad, 2014 ; Van den Hoven and Ferstl, 2018 ). Such attribution introduced by the verb can be viewed as enriched via the meaning relations that connectives establish ( Koornneef and Sanders, 2013 ; Xu et al, 2019 ; Lyu and Wang, 2022 ). For instance, implicit causality effects introduced by verbs may only hold for sentences with the connective because , but not for those with but or and ( Koornneef and Sanders, 2013 ).…”
Section: The What and How Of Ca...mentioning
confidence: 99%
“…Studies on implicit causality have demonstrated that the information encoded in the semantics of the verbs imposes constraints on causal attributions ( Crinean and Garnham, 2006 ; Bott and Solstad, 2014 ; Van den Hoven and Ferstl, 2018 ). Such attribution introduced by the verb can be viewed as enriched via the meaning relations that connectives establish ( Koornneef and Sanders, 2013 ; Xu et al, 2019 ; Lyu and Wang, 2022 ). For instance, implicit causality effects introduced by verbs may only hold for sentences with the connective because , but not for those with but or and ( Koornneef and Sanders, 2013 ).…”
Section: The What and How Of Ca...mentioning
confidence: 99%